Circulating miRNA-1290 as a potential biomarker for response to chemoradiotherapy and prognosis of patients with advanced oral squamous cell carcinoma: A single-center retrospective study - Hikaru Nakashima; Ryoji Yoshida; Akiyuki Hirosue; Kenta Kawahara; Junki Sakata; Hidetaka Arita; Tatsuro Yamamoto; Ryo Toya; Ryuji Murakami; Akimitsu Hiraki; Masanori Shinohara; Takaaki Ito; et al. (Tumor Biology)
MicroRNAs are a class of small, endogenous, noncoding 18- to 24-nucleotide-long RNAs that can regulate multiple processes related to cancer progression. However, their clinical value in patients with oral squamous cell carcinoma has not yet been fully explored. Therefore, the aim of this study was to investigate the clinical significance of circulating microRNAs in oral squamous cell carcinoma patients. The expression levels of circulating miR-1246 and miR-1290 in healthy volunteers and oral squamous cell carcinoma patients were examined by quantitative real-time polymerase chain reaction. The expression levels of both microRNAs in the radioresistant oral squamous cell carcinoma cell line (SAS-R) and the parent cell line (SAS) and in the conditioned medium obtained from these cell lines were also examined by quantitative real-time polymerase chain reaction. In addition, the correlations between circulating microRNA status and various clinicopathological features in 55 oral squamous cell carcinoma patients with locally advanced oral squamous cell carcinoma who underwent surgery following 5-fluorouracil-based chemoradiotherapy were examined. The expression level of miR-1290 was significantly lower in the plasma of oral squamous cell carcinoma patients than in that of healthy volunteers (p < 0.01). The expression levels of microRNAs in the conditioned medium and in the cells varied from cell to cell. In the clinicopathological analyses, the frequency of patients with low miR-1290 levels was significantly higher among cases with lower pathological differentiation and among those with a poor pathological response for preoperative chemoradiotherapy (p = 0.030 each). Furthermore, Cox regression analysis based on the 5-year overall survival and disease-free survival revealed that miR-1290 status was a significant prognostic factor for patients with oral squamous cell carcinoma (hazard ratio = 0.169, p = 0.008, and hazard ratio = 0.186, p = 0.008, respectively). Circulating miR-1290 status could be a valuable biomarker for predicting the clinical response to chemoradiotherapy as well as overall survival in patients with oral squamous cell carcinoma.